INTERACTIVE METHODS IN DEVELOPING MONOLOGUE SPEECH SKILLS OF STUDENTS DURING ENGLISH LANGUAGE LESSONS - Sitora Djabbarova (Journals Park Publishing, 2025)
Today, it has become commonplace to say that students need to develop general educational skills (or universal learning activities, key competencies), among which communication skills are especially highlighted. Having developed communication skills means well-developed speech, the ability to work in a group, express one’s point of view and defend it, accept someone else’s point of view, etc. The purpose of the study is to identify the possibilities of using methods in developing monologue speech skills of students during English language lessons.
Keywords: Correctness, clarity, purity, accuracy, intonation, richness, repetition, external speech, written speech, distinctive features.